ANALISA PROMOTION STRATEGY DAN ENGAGEMENT AKUN INSTAGRAM PADA HOTEL NEW AYUDA BOGOR - Christian Kuswibowo; Citra Yuniar Darmawan (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2022)
This study aims to determine the promotion strategy on Social media Instagram New Ayuda Hotel at Puncak Bogor. The analysis of the promotion strategy in this study uses the promotion mix theory which consists of 5 strategies, namely: Advertising, Personal Selling, Sales Promotion, Public Relations, Direct Marketing. This research is a type of qualitative descriptive research. Data collection methods in this study were interviews, observation, and documentation. In this study, the validity of the data was tested using a triangulation examination technique. To test the validity of the data in this study, a triangulation method was carried out by comparing information or data from observations on Instagram @newayudahotel and the results of interviews with speakers at New Ayuda Hotel at Puncak Bogor. The result of this final project is New Ayuda Hotel at Puncak Bogor in managing its Instagram using Personal Selling, Sales Promotion, Public Relations and Direct Marketing strategies. From the research data regarding the promotion strategy on Instagram @newayudahotel it is good but not optimal. Because there are some obstacles such as the lack of consistency in creating Instagram content. Therefore, it is necessary to make a planning schedule in managing Instagram @newayudahotel.